Cyclin-Dependent Kinase 1 Is Essential for Muscle Regeneration and Overload Muscle Fiber Hypertrophy - Kobayashi, Yutaka; Tanaka, Tomoyuki; Mulati, Mieradilli; Ochi, Hiroki; Sato, Shingo; Kaldis, Philipp; Yoshii, Toshitaka; Okawa, Atsushi; Inose, Hiroyuki (Frontiers in Cell and Developmental Biology, 2020)
Satellite cell proliferation is an essential step in proper skeletal muscle development and muscle regeneration. However, the mechanisms regulating satellite cell proliferation are relatively unknown compared to the knowledge associated with the differentiation of satellite cells. Moreover, it is still unclear whether overload muscle fiber hypertrophy is dependent on satellite cell proliferation. In general, cell proliferation is regulated by the activity of cell cycle regulators, such as cyclins and cyclin-dependent kinases (CDKs). Despite recent reports on the function of CDKs and CDK inhibitors in satellite cells, the physiological role of Cdk1 in satellite cell proliferation remains unknown. Herein, we demonstrate that Cdk1 regulates satellite cell proliferation, muscle regeneration, and muscle fiber hypertrophy. Cdk1 is highly expressed in myoblasts and is downregulated upon myoblast differentiation. Inhibition of CDK1 activity inhibits myoblast proliferation. Deletion of Cdk1 in satellite cells leads to inhibition of muscle recovery after muscle injury due to reduced satellite cell proliferation in vivo. Finally, we provide direct evidence that Cdk1 expression in satellite cells is essential for overload muscle fiber hypertrophy in vivo. Collectively, our results demonstrate that Cdk1 is essential for myoblast proliferation, muscle regeneration, and muscle fiber hypertrophy. These findings could help to develop treatments for refractory muscle injuries and muscle atrophy, such as sarcopenia.